Virtual microscopy of the present pathology - Słodkowska, Janina (Przewodnik Lekarza/Guide for GPs, 2008)
Telepathology (TP) is the practice of pathology at a distance, using telecommunications technology as a medium to facilitate transfer of images concerning pathology data between remote locations. TP allows quick and timely access to an expert opinion at a distance. TP has several forms and potential uses. The recent technological advances in Virtual Slides and Virtual Microscopy increased importance of TP in quality assurance, e-learning, automated image analysis and routine diagnosis. The paper presents a short overview of TP systems and models applied in various fields pathology.